2022
DOI: 10.1111/pcn.13512
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical cranial‐auricular acupoint stimulation versus escitalopram for mild‐to‐moderate depression: An assessor‐blinded, randomized, non‐inferiority trial

Abstract: Aim: Transcutaneous electrical cranial-auricular acupoint stimulation (TECAS) is a novel non-invasive therapy that stimulates acupoints innervated by the trigeminal and auricular vagus nerves. An assessor-blinded, randomized, noninferiority trial was designed to compare the efficacy of TECAS and escitalopram in mild-to-moderate major depressive disorder.Methods: 468 participants received two TECAS sessions per day at home (n = 233) or approximately 10-13 mg/day escitalopram (n = 235) for 8 weeks plus 4-week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Zhang et al [8] conducted a randomized controlled trial on the clinical efficacy and safety of transcutaneous electrical cranial-auricular stimulation (TECAS) and escitalopram in the treatment of mild to moderate depression. They found that TEAS applied at the acupoints Baihui (DU20), Yintang (EX-HN3), the auricular sites designated for the liver (CO 12 ), and heart (CO 15 ) was equivalent to escitalopram in alleviating depression and related symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [8] conducted a randomized controlled trial on the clinical efficacy and safety of transcutaneous electrical cranial-auricular stimulation (TECAS) and escitalopram in the treatment of mild to moderate depression. They found that TEAS applied at the acupoints Baihui (DU20), Yintang (EX-HN3), the auricular sites designated for the liver (CO 12 ), and heart (CO 15 ) was equivalent to escitalopram in alleviating depression and related symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Such changes in neural plasticity may help relieve anxiety and depression symptoms. [52,53] It regulates the ratio of sympathetic and parasympathetic activity, thereby reducing anxiety and depressive symptoms and improving mental health. [54] This provides a possible mechanism for ACU to treat IBS.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial of 8 weeks in 468 subjects was followed up for four weeks. The results showed that transcutaneous electrical cranial-auricular acupoint stimulation was not significantly different from escitalopram in improving depression and related symptoms, with higher safety, and special efficacy for trauma-related depression [ 51 ].…”
Section: The Effect Of Bdnf In Acupuncture For Diabetes and Depressionmentioning
confidence: 99%